2010
DOI: 10.15283/ijsc.2010.3.2.74
|View full text |Cite
|
Sign up to set email alerts
|

Application of Ultrasound Stimulation in Bone Tissue Engineering

Abstract: Many studies have been investigated on the effects of the low-intensity pulsed ultrasound (LIPUS) on bone healing, acceleration of bone mineralization and regeneration. Many researchers have focused on a more comprehensive understanding of the biological mechanism of the osteoblast by LIPUS because the osteoblast is an important cell in bone formation. The effects of LIPUS on the proliferation, gene expression of Runx2, Msx2, Dlx5, and AJ18, and the second messenger signaling of osteoblast were reported. Vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Using this intensity, the authors also reported increased bone regeneration in comparison to the control group. These results are in accordance with other reports regarding bone fracture repair, which indicate that the appropriate intensity is generally < 100 mW/cm 2 and usually in the range of 20-50 mW/cm 2 [30].…”
Section: Discussionsupporting
confidence: 93%
“…Using this intensity, the authors also reported increased bone regeneration in comparison to the control group. These results are in accordance with other reports regarding bone fracture repair, which indicate that the appropriate intensity is generally < 100 mW/cm 2 and usually in the range of 20-50 mW/cm 2 [30].…”
Section: Discussionsupporting
confidence: 93%
“…Ultrasounds are mechanical waves (sound waves) characterized by frequencies higher than the upper audible limit of the human hearing. The use of ultrasounds skyrocketed in the last decades both in diagnostics and in therapy; as for bone healing, the most used ultrasound-based technique is LIPUS (Low-Intensity Pulsed Ultrasound Stimulation), which has been tested with various successes in case of bone fractures and non-unions (Watanabe et al, 2010 ; Yang et al, 2010 ). The biology of ultrasound effects on bone tissue has been a mystery until very recently, although the role of mechanical stresses is well-known in the scientific community since a long time (Carter, 1987 ); therefore, today is universally accepted that mechanical forces are a major determinant of stem cells self-renewal and fate decision, as their roles have been assessed in embryonic and mesenchymal stem cells (Li D. et al, 2011 ).…”
Section: Endogenous Stem Cells: Current Approachesmentioning
confidence: 99%
“…Lastly, US stimulation positively influences bone tissue through biological mechanisms including cellular adhesion, proliferation, differentiation, and gene expression. Although clinical studies, such as an experiment which demonstrated a 38% decrease in the overall healing time of cortical fractures, have been conducted that validate US stimulation applications in bone tissue engineering, more research is required to develop clinical strategies [63].…”
Section: Current Strategies and Applicationsmentioning
confidence: 99%